2021
DOI: 10.1002/tox.23120
|View full text |Cite
|
Sign up to set email alerts
|

Trimetazidine improved adriamycin‐induced cardiomyopathy by downregulating TNF‐α, BAX, and VEGF immunoexpression via an antioxidant mechanism

Abstract: Few studies have reported a prophylactic effect of the anti-ischemic trimetazidine (TRI) against cardiac toxicity caused by adriamycin (ADR). However, the mechanism of action of TRI remained incomplete. The cardioprotective mechanism(s) of TRI against ADR-induced cardiotoxicity was investigated in this study. Cardiotoxicity was induced in three groups of Wistar rats by injecting a single dose of ADR (10 mg/kg, i. p.). TRI was administered in two doses regimen, low (L) (2.5 mg/kg, i.p.) and high (H) (10 mg/kg, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 41 publications
(70 reference statements)
1
9
1
1
Order By: Relevance
“…Similarly, the current study findings validate the inflammatory process associated with doxorubicin-induced cardiotoxicity, as seen by a significant rise in cardiac IL-1β and TNF-α in the doxorubicin group over the control group. These findings are consistent with other investigations (Alyasiry et al, 2022;Aziz et al, 2020;Eid et al, 2021;Rusul et al, 2022). Isosorbide dinitrate markedly decreased the elevated proinflammatory markers IL-1β and TNF-α in rats compared to the induced untreated doxorubicin group.…”
Section: Resultssupporting
confidence: 94%
“…Similarly, the current study findings validate the inflammatory process associated with doxorubicin-induced cardiotoxicity, as seen by a significant rise in cardiac IL-1β and TNF-α in the doxorubicin group over the control group. These findings are consistent with other investigations (Alyasiry et al, 2022;Aziz et al, 2020;Eid et al, 2021;Rusul et al, 2022). Isosorbide dinitrate markedly decreased the elevated proinflammatory markers IL-1β and TNF-α in rats compared to the induced untreated doxorubicin group.…”
Section: Resultssupporting
confidence: 94%
“…Additionally, it was reported that trimetazidine (TMZ), a piperazine derivative, mediated activation of the GSH system and had antioxidant and cytoprotective effects in several myocardial injury models [210][211][212][213]. For instance, in the myocardium of exhaustive-exercised rats, TMZ produced specific cardioprotective outcomes by increasing GSH and GPX activity to clear oxidative stress.…”
Section: Glutathione System Activatormentioning
confidence: 99%
“…В 2020 и 2021гг консультантами чаще назначалась дополнительная кардиопротекторная терапия триметазидином и фосфокреатином как при подготовке к хирургических вмешательствам, так и при проведении лекарственной терапии. В основе профилактического и лечебного действия триметазидина при кардиотоксичности, вызванной противоопухолевой терапией, лежат антиоксидантный, противовоспалительный и антиапоптотический эффекты препарата, обусловленные его влиянием на дыхательную цепь в митохондриях [19]. Использование фосфокреатина при ХТ больных раком молочной железы уменьшает повреждение миокарда и приводит к снижению уровней сердечного тропонина Т и С-реактивного белка [20].…”
Section: цель консультацииunclassified